"Rapid Formation, Acute Rupture" Course of Intracranial Aneurysm. Issue 8 (29th November 2022) - Bao, Ming-Yue; Ye, Lei; Cheng, Hong-Wei; Zhang, Xing
Abstract : Intracranial aneurysm (IA) is a devastating cerebrovascular disease characterizing with a potential rupturing risk. In previous studies, the formation of IA was considered to be in a chronic manner, and the ruptured aneurysms might merely derived from the already formed unruptured IA. A 61-year-old male presented to the hospital complaining of a headache. The patient received neuroimage tests, including head computed tomography and digital substraction angiography, to examine the underlying cerebrovascular diseases. Interestingly, we found a newborn ruptured IA with 9-day intervals between 2 whole-cerebral digital subtraction angiography examinations. In summary, the case in our report provides a clue for the natural course that the IA is probably in a "rapid formation, acute rupture" manner.